The bone needles from Shuidonggou locality 12 and implications for human subsistence behaviors in North China. (2nd May 2016) - Zhang, Yue; Gao, Xing; Pei, Shuwen; Chen, Fuyou; Niu, Dongwei; Xu, Xin; Zhang, Shuangquan; Wang, Huimin
Abstract: Few sites in China have yielded definite evidence for a complex bone technology. In this paper, we present a detailed description and an integrated techno-functional study of seven bone needles from Shuidonggou locality 12 dated to 12.2–11.0 ka BP in North China. Tool production processes conforming to the classic descriptions of formal techniques, including scraping, grinding, perforating, polishing and occasionally heat-treating were streamlined to process osseous materials at this site. In Shuidonggou locality 12, the bone needles manufactured accordingly were used to produce sophisticated and fitted clothing, which helps to counter winter subsistence risk, until they were very blunt or broken or no more appropriate for use, and then were discarded in situ.